2021
DOI: 10.1242/jcs.255596
|View full text |Cite
|
Sign up to set email alerts
|

DNAJB chaperones suppress destabilised protein aggregation via a region distinct from that used to inhibit amyloidogenesis

Abstract: Disturbances to protein homeostasis (proteostasis) can lead to protein aggregation and inclusion formation, processes associated with a variety of neurodegenerative disorders. DNAJBs are molecular chaperones which have been identified as potent suppressors of disease-related protein aggregation. In this work, a destabilised isoform of firefly luciferase (R188Q/R261Q Fluc; FlucDM) was overexpressed in cells to assess the capacity of DNAJBs to inhibit inclusion formation. Co-expression of all DNAJBs tested signi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 49 publications
1
28
0
Order By: Relevance
“…The small change in client affinity for DNAJB8 WT , as opposed to DNAJB8 H31Q , could be due to the enhanced proteostasis activity following stress. It was recently reported that DNAJB8 interacts with Hsp70 to promote proteasomal degradation of destabilized, aggregation-prone clients 48 . If increased protein association with DNAJB8 WT during heat shock also increases the flux of hand-off to Hsp70, then the steady state association of client proteins will only modestly change.…”
Section: Discussionmentioning
confidence: 99%
“…The small change in client affinity for DNAJB8 WT , as opposed to DNAJB8 H31Q , could be due to the enhanced proteostasis activity following stress. It was recently reported that DNAJB8 interacts with Hsp70 to promote proteasomal degradation of destabilized, aggregation-prone clients 48 . If increased protein association with DNAJB8 WT during heat shock also increases the flux of hand-off to Hsp70, then the steady state association of client proteins will only modestly change.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we aimed to determine whether we could employ the high-throughput flow cytometric analysis approach FloIT ( Whiten et al, 2016 ) to quantify the number and size of detergent-insoluble ataxin-3 particles in SCA3 cells. This method has been previously used to quantify TDP-43, SOD1 and huntingtin + inclusions ( Whiten et al, 2016 ; McAlary et al, 2016 ; Zeineddine et al, 2017a , b ), and other cellular processes associated with protein aggregation, including heat shock response induction ( San Gil et al, 2020 ), the role of molecular chaperones in suppressing protein aggregation ( McMahon et al, 2021 ) and chaperone-assisted selective autophagy ( Adriaenssens et al, 2020 ). Here, we provide the first adaption of FloIT to examine the presence of detergent-insoluble protein species in a model of spinocerebellar ataxia.…”
Section: Discussionmentioning
confidence: 99%
“…This approach has since been used to rapidly quantify the number of detergent insoluble inclusions across many in vitro models expressing aggregation-prone proteins, including mutant huntingtin (linked with Huntington's disease) ( Whiten et al, 2016 ) and motor neuron disease-linked proteins SOD1 ( Whiten et al, 2016 ; McAlary et al, 2016 ) and TDP-43 ( Zeineddine et al, 2017a , b ). The application of FloIT has also been expanded to investigate other cellular processes associated with protein aggregation, including induction of a heat shock response ( San Gil et al, 2020 ), the role of molecular chaperones in suppressing protein aggregation ( McMahon et al, 2021 ) and chaperone-assisted selective autophagy ( Adriaenssens et al, 2020 ). Considering that the formation of detergent-insoluble protein aggregates is a disease mechanism common to a wide variety of diseases, including Alzheimer's disease, Parkinson's disease, polyglutamine diseases, such as Huntington's disease and spinocerebellar ataxias, and even type 2 diabetes and dilated cardiomyopathy ( Adriaenssens et al, 2020 ; Chiti and Dobson, 2017 ; Ross and Poirier, 2004 ; Taylor et al, 2002 ; Gidalevitz et al, 2006 ; Mukherjee et al, 2015 ), it is important to determine whether FloIT can be widely adopted to study other proteinopathy disease models.…”
Section: Introductionmentioning
confidence: 99%
“…Recently developed flow cytometry approaches for quantifying protein aggregation in cellular model systems have shown great promise in providing a simple and rapid alternative to traditional methods (Hidalgo et al 2016; McMahon et al 2021; Ramdzan et al 2012; Shiber et al 2014; Whiten et al 2016). In this study, we describe a method that enables fluorescent inclusions to be enumerated and characterised in C. elegans by exploiting a standard flow cytometry setup.…”
Section: Discussionmentioning
confidence: 99%
“…This technique also has the advantage of allowing for the quantification of nuclear flux of fluorescently-tagged proteins. The application of flow cytometric analyses to quantify inclusions has been demonstrated to be a powerful tool for cell-based studies as they are unbiased and can be applied to high-throughput screens (McMahon et al 2021; Whiten et al 2016). However, a method exploiting flow cytometry to quantify inclusions formed in C. elegans has not yet been described.…”
Section: Introductionmentioning
confidence: 99%